2016
DOI: 10.1016/j.jenvrad.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

The transfer of radiocesium from the bark to the stemflow of chestnut trees (Castanea crenata) contaminated by radionuclides from the Fukushima Dai-ichi nuclear power plant accident

Abstract: We report on the behavior of radiocesium in tree bark and its transfer into the stemflows of chestnut trees in a forest in the Fukushima Prefecture, Japan. In stems that were present at the time of the accident, the radiocesium concentration of the bark was found to be approximately 10 times that of the wood. The average (137)Cs concentration of the dissolved fraction (<0.45 μm) in the stemflow was measured to be around 10 Bq/L. The (137)Cs concentration ratio [present at the time of the accident (Bq/kg) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Similar broad distributions of radiocaesium were also found in the leaves of bamboo plants and samples from chestnut trees collected in Fukushima prefecture within three years after the Fukushima nuclear accident, although some spotty distributions were also observed [37,38]. Soudek et al [39] studied 137 Cs distributions in sunflower with hydroponic culture experiments using 137 CsCl solution.…”
Section: Plos Onementioning
confidence: 63%
“…Similar broad distributions of radiocaesium were also found in the leaves of bamboo plants and samples from chestnut trees collected in Fukushima prefecture within three years after the Fukushima nuclear accident, although some spotty distributions were also observed [37,38]. Soudek et al [39] studied 137 Cs distributions in sunflower with hydroponic culture experiments using 137 CsCl solution.…”
Section: Plos Onementioning
confidence: 63%
“…The average 137 Cs concentration of the dissolved fraction (< 0.45 μm) in the stemflow was measured to be around 10 Bq·L −1 (Sasaki et al, 2016). This result indicated that radiocesium deposited to the bark was eluted as dissolved radiocesium.…”
Section: Resultsmentioning
confidence: 92%
“…Fallen leaves were collected immediately after defoliation in November 2013. Chestnut tree samples were obtained from branches of the canopy at a height of approximately 7 m in February 2014 (Sasaki et al, 2016).…”
Section: Samplingmentioning
confidence: 99%
“…137 Cs was previously suggested to be absorbed and retained on bark surfaces due to the dead tissues in the outer bark [ 29 ]. In case of the FDNPP accident studies, radiocaesium was also distributed on the outer surface of barks [ Castanea crenata (chestnut tree) and Cryptomeria japonica (Japanese cedar)], sampled within the Fukushima Prefecture [ 47 , 48 ]. In addition, most of the radiocaesium in barks was found in the outer bark of cherry trees (30 years old) [ 48 ].…”
Section: Resultsmentioning
confidence: 99%